1997
DOI: 10.1038/hdy.1997.124
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and spatial structure within a natural stand of a tropical forest tree species, Carapa procera (Meliaceae), in French Guiana

Abstract: Isozyme markers were used to characterize levels of diversity, genotypic structure and spatial genetic structure for the low-density tree species, Carapa procera (five adults per ha), within 300 ha of a continuous tropical rain forest stand. Both seed and adult stages were investigated, a high level of genetic diversity being found in both. Fixation indices showed excess homozygosity in seeds, and excess heterozygosity in adults, which might be caused by selection in favour of heterozygotes. Autocorrelation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 43 publications
2
42
2
5
Order By: Relevance
“…In a study on spatial genetic structure of Carapa procera no spatial structure was found for allozymes in Paracou (Doligez and Joly 1997). In contrast, the present study detected significant spatial structure for RAPDs up to 150m.…”
Section: Relation Between Spatial Structure and Pollen And Seed Dispecontrasting
confidence: 99%
See 1 more Smart Citation
“…In a study on spatial genetic structure of Carapa procera no spatial structure was found for allozymes in Paracou (Doligez and Joly 1997). In contrast, the present study detected significant spatial structure for RAPDs up to 150m.…”
Section: Relation Between Spatial Structure and Pollen And Seed Dispecontrasting
confidence: 99%
“…1995;Caron et al 1998;Doligez and Joly 1997;Hamrick et af. 1995;Caron et al 1998;Doligez and Joly 1997;Hamrick et af.…”
Section: Introductionunclassified
“…Therefore, the species' strong self-incompatibility probably accounts for the high outcrossing rates observed in the low density stands here. The overall estimate of effective number of pollen donors (N ep ), 7.0, was similar to estimates obtained for other hardwood species, which are generally lower than 12 (Doligez and Joly 1997;Smouse et al 2001). Trends of N ep calculated from U FT and r p were similar to those observed in the seed set and germination of dispersed seed rates.…”
Section: Pollen Flowsupporting
confidence: 67%
“…Many studies on plants have been devoted to characterizing SGS (Heywood 1991;Epperson et al 1999;Mantovani et al 2006;Hardy et al 2006;Born et al 2008), because the presence of SGS within populations has important implications in conservation programs as it can affect estimates of genetic parameters (Young and Boyle 2000;Jones and Hubbell 2006), such as the outcrossing rate in natural populations (Ennos and Clegg 1982;Bittencourt and Sebbenn 2007), influencing the sampling strategies for improvement of conservation projects ex situ and it aids management of populations, where exploitation patterns can affect the levels of genetic diversity (Doligez and Joly 1997;Sebbenn et al 2008).…”
Section: Introductionmentioning
confidence: 99%